2002
DOI: 10.1007/s00244-001-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tetrachloroethylene on the Viability and Development of Embryos of the Japanese Medaka, Oryzias latipes

Abstract: We evaluated the acute toxicity of Tetrachloroethylene (C(2)Cl(4)), and investigated its sub-chronic effects on the embryonic development of Japanese medaka (Oryzias latipes). One-day-old eggs/embryos of this fish species were exposed, under static renewal conditions, to serial concentrations (0, 20, 40, 60, and 80 mg/L) of C(2)Cl(4) for 96 h (acute) and 10 days (sub-chronic) time periods. The toxic endpoints evaluated included: egg/embryo viability, hatchability, and morphological/developmental abnormalities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In the embryo-larval development, the effects of xenobiotics on hatching rate is due to the exertion of toxicity response which disturbs enzymatic pathways in morphological and physiological processes at this vital stage of their life cycle. The delay in the hatching rate of the diuron-exposed embryos in this study was in line with Spencer et al [54], which reported that exposure of Japanese medaka (Oryzias latipes) to tetrachloroethylene (PCE), a potential EDC delayed hatching. Kao et al [55] demonstrated that the survival rate and hatching rate of Danio rerio embryos were considerably unaffected after exposure to diuron in comparison to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In the embryo-larval development, the effects of xenobiotics on hatching rate is due to the exertion of toxicity response which disturbs enzymatic pathways in morphological and physiological processes at this vital stage of their life cycle. The delay in the hatching rate of the diuron-exposed embryos in this study was in line with Spencer et al [54], which reported that exposure of Japanese medaka (Oryzias latipes) to tetrachloroethylene (PCE), a potential EDC delayed hatching. Kao et al [55] demonstrated that the survival rate and hatching rate of Danio rerio embryos were considerably unaffected after exposure to diuron in comparison to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…For example, exposure to atrazine and ametrine herbicides resulted in increased MN [55]; in contrast, a different herbicide, pendimethalin, showed increased ENA but not MN [56]. Tetrachloroethene, the only CEC analyzed that presented higher concentrations in P2 than P1, is a dry-cleaning compound widely used in the textile industry, known to have toxic effects in fish [57,58]. Although evidence in humans supports the link between the MN formation and this compound [59], to the authors’ knowledge, there are no published studies demonstrating this association in fish.…”
Section: Discussionmentioning
confidence: 99%
“…In continuation of our studies on the effects of environmental pollutants on Japanese medaka fish 18–19 , a small laboratory fish, considered as complementary to zebrafish 20 , we studied the potential toxic effects of OXY, an herbicide, widely used in agriculture. This compound is almost insoluble in water (0.116 mg/L at 25 °C); to improve the solubility of OXY in ERM or BSS, we used 0.1% acetone as a solvent and parallel control embryos/larvae were maintained in 0.1% acetone-containing media as vehicle control in addition to the normal control maintained in ERM.…”
Section: Discussionmentioning
confidence: 99%